Impact of Cohb Exposure on Diabetes Mellitus Incidence in Tanjung Sari Village - Estikho Maharani; Sutrisno (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Diabetes Mellitus (DM) is a non-communicable disease whose prevalence continues to rise in Indonesia. Based on routine Puskesmas reports, there has been an increase in the number of patient visits with DM-related complaints over the past two years, with individuals with metabolic risk factors and certain environmental exposures tending to dominate this group. Furthermore, Tanjung Sari Village is located close to busy traffic routes and household combustion activities, which have the potential to increase carbon monoxide (CO) exposure, potentially leading to increased carboxyhemoglobin (COHb) levels in the community, even though the majority are non-smokers. The purpose of this study was to determine the relationship between COHb levels and the incidence of diabetes mellitus in Tanjung Sari Village, within the Tanjung Sari Natar Community Health Center (Puskesmas). Method: This study used a quantitative cross-sectional design. The population was 53 DM patients aged 12-30 years seeking treatment at the Tanjung Sari Natar Community Health Center (Puskesmas). The sample used was a purposive sampling method. This research was conducted in August 2025. Data collection was conducted using observation sheets and data analysis using a computer program, with the Gamma test used for analysis. Result: The results of the study revealed a significant relationship between COHB levels and the incidence of diabetes in Tanjung Sari Village, within the Tanjung Sari Natar Community Health Center (Puskesmas) in 2025, with a p-value of 0.000 (p < 0.05). Conclusion: The conclusion is that there is a relationship between COHB levels and the incidence of diabetes. The Community Health Center can conduct regular education to the community about the dangers of CO exposure and its relationship to metabolic diseases, including diabetes.